Rigid-body ligand recognition drives cytotoxic T-lymphocyte antigen 4 (CTLA-4) receptor triggering. - Yu, C; Sonnen, A; George, R; Dessailly, B; Stagg, L; Evans, E; Orengo, C; Stuart, D; Ladbury, J; Ikemizu, S; Gilbert, R; Davis, S (2011)
The inhibitory T-cell surface-expressed receptor, cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), which belongs to the class of cell surface proteins phosphorylated by extrinsic tyrosine kinases that also includes antigen receptors, binds the related ligands, B7-1 and B7-2, expressed on antigen-presenting cells. Conformational changes are commonly invoked to explain ligand-induced "triggering" of this class of receptors. Crystal structures of ligand-bound CTLA-4 have been reported, but not the apo form, precluding analysis of the structural changes accompanying ligand binding. The 1.8-Å resolution structure of an apo human CTLA-4 homodimer emphasizes the shared evolutionary history of the CTLA-4/CD28 subgroup of the immunoglobulin superfamily and the antigen receptors. The ligand-bound and unbound forms of both CTLA-4 and B7-1 are remarkably similar, in marked contrast to B7-2, whose binding to CTLA-4 has elements of induced fit. Isothermal titration calorimetry reveals that ligand binding by CTLA-4 is enthalpically driven and accompanied by unfavorable entropic changes. The similarity of the thermodynamic parameters determined for the interactions of CTLA-4 with B7-1 and B7-2 suggests that the binding is not highly specific, but the conformational changes observed for B7-2 binding suggest some level of selectivity. The new structure establishes that rigid-body ligand interactions are capable of triggering CTLA-4 phosphorylation by extrinsic kinase(s).